Best Answer

x+y=15

4x+3y=38

4x+4y=60

4x+3y=38

(4x+4y=60)-(4x+3y=38)-->

(4x-4x+4y-3y=60-38)-->

(0x+1y=22)-->

[since 0x=0]

(1y[y]=22)

given y=22

and x+y=15

x+22=15

x=15-22=-7

therefore ANSWER KEY

X=-7 Y=22

Checking answers

4x+3y=38

-28+66=38

THEREFORE

This is correct

If you have problems please write a message on Its Me Ue's message board

Q: What is x plus y equals 15 in 4x plus 3y equals 38?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

(1) x+y=15(2) 4x+3y=38From (1) one gets x=15 -y, put into(2)4(15-y)+3y=3860-4y+3y=3860-y=38y=22 then x=15-y=-7(-7,22) is the solution

x+y=15, or y=15-x4x+3y=38Substitute y in 2nd equation with 15-x:4x+45-3x=38x=-7y=15-(-7)=22(-7,22)

7

yes

rewrite first equation: x = 15 - y substitute into second equation for x: 4(15 - y) + 3y = 38 distribute and simplify: 60 - y = 38 solve: y = 22 plug back into first equation: x = -7 -OR- multiply first equation by -3: -3x - 3y = -45 add new equation to second equation: 1x + 0y = -7 or x = -7 plug back into first equation: y = 22

Related questions

4.34684352143

(1) x+y=15(2) 4x+3y=38From (1) one gets x=15 -y, put into(2)4(15-y)+3y=3860-4y+3y=3860-y=38y=22 then x=15-y=-7(-7,22) is the solution

x+y=15, or y=15-x4x+3y=38Substitute y in 2nd equation with 15-x:4x+45-3x=38x=-7y=15-(-7)=22(-7,22)

7

x + y = 154x + 3y = 38from the first equation, y = 15-xsubstitute this value in the second equation as follows:4x + 3(15-x)= 384x + 45 - 3x = 38x + 45 = 38x = 38 - 45so, x = -7substitute this value to solve for y:y = 15 -xy = 15-(-7)y = 22

yes

80 = 3y + 2y + 4 + 1 75 = 5y 15 = y y = 15

rewrite first equation: x = 15 - y substitute into second equation for x: 4(15 - y) + 3y = 38 distribute and simplify: 60 - y = 38 solve: y = 22 plug back into first equation: x = -7 -OR- multiply first equation by -3: -3x - 3y = -45 add new equation to second equation: 1x + 0y = -7 or x = -7 plug back into first equation: y = 22

The solution pair is (-7, 22), demonstrated as follows: (1) x + y = 15 : given; (2)4x + 3y = 38 : given; (3)3x + 3y = 45 : equation (1), multiplied by 3; (4) x = -7 : equation (2), minus equation (3); (5) y = 22 : equation (1), minus equation (4).

OK, so-3y + 15 - y = 39-3y + 15 - 15 - y = 39 - 15-3y -y = 24-4y = 24-y = 6y= -6.Hope this helps!

3y+5=y-25 2y=-30 y= -15

(2,7)